Begnadung als berechtigte Forderung?: Gedanken zur Bedeutung des übernatürlichen Existentials in der Gnadenlehre Karl Rahners - Keppeler, Cornelius (Zeitschrift für katholische Theologie, 2004)
The present article gives a small introduction to the terminology of Rahner's theology of grace. The different positions of Henri de Lubac and Karl Rahner are recalled and related to each other with particular attention given to the conflict about the relation of nature and grace. Rahner elucidates this relation by distinguishing »natura pura«, »potentia oboedientialis«, »supranatural existential« and »grace«, giving in neither to intrinsicism nor to extrinsicism. The study argues that the difference of opinions of de Lubac and Rahner is small. There are problems of communication and accentuation in their arguments but no contrary points of view. In addition, the author shows that Paul Rulands' construction of the »supranatural existential« in Rahner's early works neglects the terminological influence of Heidegger. An interpretation considering this philosophical background confirms the criticized consensus.